Improvement of the functional pavement quality with asphalt rubber mixtures - Fontes, Liseane P. T. L. (2006)
Skid resistance and texture are important safety characteristics which need to be considered in flexible pavement design, maintenance and rehabilitation. The main objective of this paper is to optimize surface texture characteristics in asphalt rubber pavements, mainly macrotexture to reduce splash, spray and hydroplaning and microtexture to increase friction at low and high speeds. The objective was accomplished by measuring the friction surface with two different tests: (i) British pendulum; (ii) Volumetric Method. The specimens prepared in the laboratory represent the as-constructed pavement surface. In this study, two different mixtures grading (dense and gap) were produced using three types of binders: (i) conventional asphalt; (ii) asphalt rubber using terminal blend process; (iii) asphalt rubber using continuous blend process. The binder content influence in functional quality was tested by using the same configuration for mixtures with more 1% of asphalt rubber content. The results of this study were carried out to evaluate the effect of asphalt rubber production process and mixtures gradation on the pavement surface characteristics. The results showed that the mixture with gap grading exhibit higher texture in comparison of mixtures with a dense grade gradation. The asphalt rubber mixtures improved the skid resistance compared to conventional mixtures. This research indicates that the CRM (crumb rubber modified) production with rubber from the different processes have significant differences in pavement surface characteristics.